PENDIDIKAN KARAKTER DALAM AL-QURAN SURAT AL-HUJURAT - Zulkarnain S (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2016)
Alquran al-Hujurat contain  values which can be a reference to a character in a character education in Indonesia, which is facing a moral crisis. The type is library research with critical analytical method and analytic interpretation.The Issues  raised  are:  how  al - Hujurat  reveal  character education?, what  values  of character education are  contained in it? and  what  are  the  implications of character education in Surat  al - Hujurat  in the  world  of education? The  results  showed that  the  character education contained in al-Hujurat  included manners to God, to the Prophet Muhammad and to his fellow man  of him. There are values of commendable character and values of despicable character in it. Implications of character education in al-Hujurat to the world of education is that educators (teachers) and learners (students) must adhere to the ethics code of teachers and pupils.